The press in the area of Geography, History, and Social Sciences (Journal of Parents and Teachers, 2025)
The article describes the Basic Curriculum Design and the sections in which it is differentiated: introduction (the newspaper, essential), blocks (the newspaper, conditioning), teaching guidelines (prominent place), and evaluation guidelines (presence of mass communication sources).
Keywords: DCB; blocks; newspaper; guidelines